Pengalaman Psikologis Warga Binaan Selama Menjalani Masa Hukuman di Lembaga Permayarakatan Kelas III Kota Banjar - Aneng Yuningsih; M Arif Hidayat; Reni Hertini (Jurnal Medika Cendikia, 2019)
Individuals have different reactions in dealing with stress, depending on various psychological factors such as how individuals look at events that cause stress. When living in a correctional facility (Lapas), the space for movement is limited, isolated from the community, feelings of guilt, loss of freedom, feelings of shame, economic sanctions, social sanctions and length of detention adds to psychological stressors for inmates. This study aims to explore the Psychological Experiences of Fostered Citizens During Their Sentencing in Class III Penitentiary in Banjar City. This study uses a qualitative design with a transcendent phenomenological approach that focuses on the universal part of individual experience. The research sample of five participants using purposive sampling. Data collection method is done through in-dept interview with data analysis using content analysis. From the results of the research analysis identified six themes, namely: Error, Regret, Sadness, Want to Be Better, Disappointed, and the Meaning of Life Experience. Based on this research it can be concluded that participants consider what they have done is a mistake, now participants regret what they have done, participants feel sad and want to be better in the future, and participants assume what has happened now is a valuable life experience to be even better in the future.